Ativação astrocitária em estágios iniciais de um modelo animal de parkinsonismo progressivo induzido por reserpina - Santos, Edson de Rezende (2018)
Parkinson's disease (PD) is a chronic neurodegenerative disorder with a broad spectrum of motor (SM) and non-motor (NMS) symptoms resulting from a neurodegeneration process in multiple systems of central neurotransmission. Glial cells such as astrocytes appear to be involved in this process; however, little is known about the early involvement these cells in the development or progression of the disease. Therefore, the aim of this study was to evaluate the participation of astroglia in the model of progressive parkinsonism induced by low doses of reserpine (RES). Forty – two seven – nine month-old Wistar rats were used. Animals were randomly allocated to two experimental groups: control (animals treated with vehicle solution) and RES (animals treated with reserpine 0.1 mg / kg), n = 21 per group. Animals from both groups received 4, 10 or 15 subcutaneous injections (s.c.) of vehicle or RES every other day. Forty-eight hours after the 4th (n = 7 per group), 10th (n = 7 per group) and 15 (n = 7 per group) injections, animals were perfused for immunohistochemistry analysis to glial fibrillary acid protein (GFAP) and tyrosine hydroxylase (TH) in the brain. The Animal Research Ethics Committee of the Federal University of Sergipe, under protocol number 10/2017, previously approved the experimental procedures. In the catalepsy test, an increase in bar stay time was observed for animals in the RES group when compared to the control group 48 hours after the 5th injection (p = 0.005) and were maintained until the end of the treatment. In the test of the tape, the RES group showed an increase in the removal time (48 h after the 4th injection of RES (p = 0.048) and perception of the adhesive (48 h after the 8th injection of RES (p = 0.004), the end of the experiment. In the dorsal striatum (ED), but not in the substantia nigra pars compact (SNpc), in the dorsal raphe nucleus (DRN) and locus coeruleus (LC) of RES group, an increase in the number and density of GFAP+ , 48 h after the 4th injection (p <0.001) was observed. These data remaining until the end of the treatment, accompanied by a decrease in astroglial length 48 h after the 10th injection (p = 0.017) and 15th injections (p = 0.041). In the SNpc, a reduction of TH immunoreactive cells was observed in the animals treated with RES after the 10th (p = 0.026) and 15th (p = 0.038) injections. Besides, TH immunoreactive also decreased in the ED (p = 0.014) and in the ventral tegmental area (VTA) (p = 0.014) after the 15th injection; in the locus coeruleus after the 4th (p = 0.005) and the 15th injection (p = 0.046) and in the DRN, after the 4th (p = 0.016), but not after the 10th (p = 0.445) and 15th injections (p = 0.559). These data show that the increase in astrocytic activation occurs even before the motor alterations suggesting that these cells play an important role in the pathophysiology of PD, even in the early stages.